Sistem Pengaturan Suhu Air Menggunakan Kendali PID berbasis LabVIEW - Ari Ramadhani (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2016)
Abstract - Automatic system have grown widespread across all sector so do water heater. Traditionally, heating water is done by utilizing fire as heat source. As the growing of technology, the heating process could be done by manipulating electrical energy by convert it to heat. Electrical energy is flown to a metal rod that contact directly with the water which increase the water temperature. On some case, appropiate water temperature is needed. Altough, a thermometer is needed to read the actual temperature as a feedback value for the system and a system that can control the electricity current flow through the heater that the heat produced is linear to the current flow. With implementing microcontroller as a process node for generating PWM signal, this problem can be solved. Also, Labview is needed as an interface for monitoring and bursting an output which have been processed by Proportional, Integral, and Devivative (PID) controller to producing accurate and stable heat. Based on the results of testing, the system is able to provide a rapid response to any changes that occur, both changes in set-point and changes in water temperature (actual value). Another test is done by comparing the temperature value detected by the temperature sensor in this device with an external digital thermometer placed in the same place, and from some of the tests the temperature value detected by the temperature sensor in this device has a difference of Â± 0.19 â„ƒ with a digital thermometer. Keyword : Water Heater, Thermometer, Microcontroller, LabView, PID.